The Correlation Between Feeding Parenting Practices and Infectious Diseases with The Incidence of Stunting Among Children Aged 24–59 Months (in The Working Area of Lampihong Public Health Center) - Raudatuljanah Raudatuljanah; Ermina Syainah; Siti Mas’Odah (Lembaga Pengembangan Kinerja Dosen, 2026)
Stunting is a chronic nutritional problem that remains a public health challenge. The prevalence of stunting in the working area of Lampihong Health Center in 2024 was 21.05%This study aimed to analyze the relationship between feeding parenting practices and infectious diseases with the incidence of stunting among children aged 24–59 months. This study was an analytic observational study using a cross-sectional design. The population consisted of all children aged 24–59 months in the working area of Lampihong Health Center, with a sample of 87 children. Data were collected through anthropometric measurements, interviews using the Child Feeding Questionnaire (CFQ), and assessment of infectious disease history. Data analysis was conducted using the chi-square test with a 95% confidence level. The results showed that the prevalence of stunting was 37.9%. Most children were aged 24–35 months (57.5%) and were male (63.2%). Appropriate feeding practices were identified in 55.2% of respondents, while 65.5% of children had a history of infectious diseases. Bivariate analysis demonstrated a significant association between feeding parenting practices and stunting (p < 0.001), as well as between a history of infectious diseases and stunting (p < 0.001). It was concluded that inappropriate feeding parenting practices and infectious diseases play a significant role in the occurrence of stunting among children aged 24–59 months. It is expected that health workers will be more active in addressing the stunting problem by improving health education activities and conducting regular growth monitoring at posyandu.